(-)-Epicatechin and β-glucan from highland barley grain modulated glucose metabolism and showed synergistic effect via Akt pathway. (December 2021) - Liu, Ze-Hua; Li, Bo
Graphical abstract: Highlights: (-)-Epicatehin and β glucan were the active compounds in highland barley grain that modulated glucose metabolism. (-)-Epicatehin targeted IRβ receptor and regulated IRS-1/PI3K/Akt pathway to modulate glucose metabolism. Beta glucan targeted mTOR receptor and regulated Akt pathway to modulate glucose metabolism. Combination of (-)-epicatehin and β glucan synergistically improved glucose uptake and glycogen synthesis, and inhibited gluconeogenesis via Akt pathway. Abstract: In this study, (-)epicatechin (EC) and β-glucan (BG) were identified as the active compounds in highland barley grain that modulated glucose metabolism. The mechanism underlying EC may target on insulin receptor and regulate target on insulin receptor substrate-1 /phosphatidylinositol 3-kinase / protein kinase B (Akt) pathway, and BG may target on mammalian rapamycin receptor and regulate the Akt pathway. EC and BG showed anti-hyperglycemic effects and modulated hepatic glucose metabolism in mice with impaired glucose tolerance. Moreover, EC combined with BG showed synergistic effects on the Akt pathway, thereby improved glucose uptake through up-regulating glucose transporter 4, improved glycogen synthesis by down-regulating glycogen synthase kinase-3β, and inhibiting gluconeogenesis by down-regulating phosphoenolpyruvate carboxykinase 1 protein expression. These results provide evidence of a whole highland barley grain diet to prevent type 2 diabetes or developing EC and BG as new dietary supplement.